PENGARUH TANGGUNG JAWAB SOSIAL DAN GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PADA PERUSAHAAN CONSUMER GOODS INDUSTRY - Herni Puspitaningrum Yanuar Puspitaningrum; Astiwi Indriani (JURNAL STUDI MANAJEMEN ORGANISASI, 2022)
The aim of this study is to investigate the effect of corporate social responsibility and good corporate governance on the firm's profitability. The proxies used in this study are the CSR index for corporate social responsibility, the board of commissioners size, board of commissioners education, board of directors size, and board of directors education for good corporate governance. In addition, this study also uses company size and leverage as control variables.This research collected sample data with a purposive sampling method and found 32 companies from a total population of 63 consumer goods industry companies listed on the Indonesia Stock Exchange for the period of 2016-2019. This study used secondary data taken from the official website of the Indonesia Stock Exchange with multiple linear regression analysis methods.The results of this study indicate that there is a significant positive effect between the board of commissioners size and board of directors education on the firm's financial performance as proxied by ROA, and a significant negative effect between corporate social responsibility index, board of commissioners education, and board of directors size on the firm's financial performance.